Comparative Evaluation of Shear Bond Strength of Bioactive Restorative Material, Zirconia Reinforced Glass Ionomer Cement and Conventional Glass Ionomer Cement to the Dentinal Surface of Primary Molars: an in vitro Study - Komal Nanavati; Farhin Katge; Vamsi Krishna Chimata; Debapriya Pradhan; Aishwarya Kamble; Devendra Patil (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: The success of dental restorations depends mainly on its ability to bond to dental structures and resist the multitude of forces acting on it within the oral cavity. Purpose: Therefore, the aim of this study was to evaluate the shear bond strength (SBS) of three different glass ionomer based restorative materials. Materials and Method: In this in vitro analytical study, 30 intact primary molars were sectioned buccolingually to obtain 60 sections. These sections were embedded in auto polymerizing acrylic resin and polished to obtain a flat dentin surface. Restoration cylinders were built on the dentin surface with the help of a Teflon template called bonding jig. Each group (n= 20) was restored as group A with conventional glass ionomer cement (GIC) (GC Fuji Gold Label Type 9), group B with Bioactive restorative material (ACTIVATM KIDS BioACTIVE Restorative material), and group C with Zirconia reinforced glass ionomer cement (Zirconomer). Following restoration, SBS testing was performed using Universal Testing Machine. The data obtained were statistically analyzed using One way ANOVA test and post hoc Tukey test (p= 0.05). Results: The SBS values were significantly greater in the ACTIVA KIDS group as compared to the other two groups (p< 0.05). There was no significant difference in the SBS values between group B and group C (p> 0.05). Conclusion: The SBS of the ACTIVA KIDS to primary teeth dentin was the highest as compared to Zirconomer and conventional GIC. Therefore ACTIVA KIDS may protect primary teeth against recurrent caries and failure of the restoration.